Repozytorium instytucjonalne jako czynnik wspomagający rozwój nauki w środowisku akademickim - Rychlik, Małgorzata; Karwasińska, Emilia (My University, 2007)
Now that much of the civilized world is pursuing information that interests, appeals and enriches knowledge, the development of science and research can only be maintained if access to relevant publications and a possibility of sharing the knowledge on the results and conclusions of carried out research are properly secured. Addressing the demands emphasizing indispensable right of man to education and information formulated by the academic community, the idea of Open Access (of free and unlimited access to publications in science and the humanities) has followed. The article discusses setting up relevant repositories with a particular emphasis on institutional repositories at universities. The advantages and disadvantages of the idea are evaluated and discussed as well as relevant legal aspects and the place the institutional repository can occupy in scientific communication. The intention of the authors is to persuade the academic and scientific community in Poland to participate in setting up repositories, which would substantially enrich the propagation of knowledge and, within a given time perspective, enhance its better development.
The institutional repository as an element supporting the development of science and the humanities within the academic community
Keywords: Repozytorium instytucjonalne; Open Access; Institutional repository; Komunikacja naukowa; Scientific communication